150 Osteoporosis Risk Factors in Children with Cerebral Palsy. (29th October 2021) - Spenard, Sarah; Rahman, Arifur; Power, Heather; O'Dea, Jennifer; Ricci, M Florencia
Abstract: Primary Subject area: Complex Care Background: Cerebral palsy (CP) is a common motor disability in children. Due to their medical complexity, children with CP are prone to osteoporosis, and consequently, fractures. The prevalence of osteoporosis and its risk factors are poorly understood within this population. Objectives: To determine the prevalence and predictors of osteoporosis among a provincial cohort of Canadian children with CP. Design/Methods: We performed a retrospective descriptive cohort study in a single Canadian tertiary care pediatric hospital. The medical charts of the 187 children with CP currently followed by the rehabilitation team were reviewed. Primary outcomes were indicators of osteoporosis, including vertebral compression fractures (VCF), long bone fractures and BMD Z-score. Osteoporosis risk factors, including medications, chronic or endocrine disorders linked to secondary osteoporosis, feeding method, and mobilization level (GMFCS), were collected. Two-tail p-values were calculated using the Chi-squared Person's cumulative test. Results: Of the 187 included children, the majority were male (59%) and were living in a rural area (62%). Seven (3.7%) individuals met diagnostic criteria for osteoporosis with a VCF without history of high-energy trauma or local disease. Of these, four were females and three were males. Osteoporosis risk factors are presented in Table 1. GMFCS, feeding method and medications linked to secondary osteoporosis had a significant statistical difference in the children diagnosed with a VCF compared to participants without osteoporosis diagnostic criteria. Conclusion: 3.7% of children followed by the provincial rehabilitation team have osteoporosis. This is one of the first studies that establishes the frequency of osteoporosis among a provincial cohort of Canadian children with CP. Mobilization level, feeding method and consumption of medications linked to secondary osteoporosis seem to be major risk factors for osteoporosis in children with CP. Larger prospective studies are needed to confirm this association, in order to improve prevention strategies.